HUBUNGAN ANTARA MEMAAFKAN DENGAN KEMATANGAN DIRI PADA REMAJA AKHIR - Sumiati, Ilsan; Sandjaja, Stefanus Soejanto (Noetic Psychology, 2017)
Abstract. This study aimed to determine the relationship between self-maturity and forgiveness in the late adolescence. The hypothesis of this study was there is a positive correlation between self-maturity and forgiveness in the late adolescence. The population in this study were university students at UKRIDA. The research sample was taken by purposive sampling (N=108 subjects). This study used quantitative approach. The data were collected using a scale. The instruments that used in this study were forgiveness scale TRIM-18 (Transgression Related Interpersonal Motivation) and Self-Maturity scale. The data were analyzed by PearsonÃ¢â¬â¢s Product Moment correlation analysis. The result showed, that there is a positive relationship between self-maturity and forgiveness in late adolescence (r = 0.491; p < 0,01).Keywords: forgiveness, late adolescence, self-maturity